Mothers' perception and attitude regarding thalassemia among children in Bangladesh - Dipa Samadder; Tumpa Gharami; Halima Akter (Nursing and Health Sciences Journal (NHSJ), 2025)
Thalassemia, a prevalent genetic disorder in Bangladesh, poses a heavy burden on families and the healthcare system. This thesis examines the perceptions and attitudes of mothers towards thalassemia in children, aiming to understand their knowledge of the disease, coping mechanisms, and interactions with healthcare providers. The study aimed to evaluate the maternal understanding and attitudes concerning thalassemia in children in Bangladesh. A cross-sectional study was conducted with 112 mothers from the pediatric ward and outpatient department at Sher-e-Bangla Medical College Hospital, Barisal. A convenience sampling method was employed to select participants. Data were gathered using a structured questionnaire divided into three sections and analyzed using SPSS version 25. Descriptive statistics (frequency, percentage) and inferential statistics (t-test, ANOVA, Correlation) were applied for analysis. The average age of participants was 27 years (SD=5.822). The total mean perception (30.33±10.647) and attitude (18.80±5.451) levels were moderate and high among this study’s respondents, respectively. There was a significant negative correlation between participants' age and their perception of thalassemia (r= -0.203, p=0.032). Statistically significant relationships were also found between participants' religion and perception (F=10.106, p=0.000), occupation level and perception (F=4.224, p=0.007), and residential area and perception (t=-2.442, p=0.016). The findings revealed a strong association between sociodemographic factors and mothers' perceptions and attitudes about thalassemia. Raising awareness through educational campaigns and prevention programs could help control thalassemia. Educated mothers are better equipped to provide care, improving health outcomes for children with thalassemia.